2003
DOI: 10.1074/jbc.m210249200
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Regulation by Rac and Rho of Agrin-induced Acetylcholine Receptor Clustering in Muscle Cells

Abstract: During embryonic development, innervation induces the anatomical and biochemical specialization of a defined region of the muscle cell membrane immediately under the motor nerve ending. A prominent aspect of this specialization is the accumulation of high densities of nicotinic acetylcholine receptors (AChR) 1 at these sites (1, 2). The aggregation of AChR and other synaptic components is mediated by agrin, a heparansulfated proteoglycan that is synthesized by motor neurons and secreted into the synaptic cleft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
104
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 51 publications
9
104
3
Order By: Relevance
“…This result was in line with a previous report (12), except the elapsed time here is slightly shorter, which could be a result of the difference in myotube species. Weston et al (12) used C2C12 myotubes, and we used primary chick myotubes. In addition, this time course of RhoA activation was very similar for both types of assays in measuring RhoA activation.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…This result was in line with a previous report (12), except the elapsed time here is slightly shorter, which could be a result of the difference in myotube species. Weston et al (12) used C2C12 myotubes, and we used primary chick myotubes. In addition, this time course of RhoA activation was very similar for both types of assays in measuring RhoA activation.…”
Section: Resultssupporting
confidence: 83%
“…Moreover, Rac is proposed to play a role in the formation of agrin-induced small AChR aggregates; RhoA is required, subsequently, to condense those small aggregates as large agrin-induced AChR aggregates. The small GTPases are known to induce the re-arrangement of intracellular cytoskeleton (40), which, therefore, could explain the clustering of AChRs in the post-synaptic muscle (12,41). Here, we demonstrate further the potentiation role of P2Y 1 receptor in agrininduced AChR aggregation could also involve the small GTPases.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…This effect is mediated through sequential activation of Rho GTPases; agrin induces a rapid and transient activation of Rac1 that is necessary for the initial phase of AChR micro-cluster formation, whereas the subsequent RhoA activation is crucial for the coalescence of the micro-clusters into full-sized AChR clusters (11,12). Although initial evidence suggested that agrin was crucial for initiation of post-synaptic development (6,7), agrin also plays a later maintenance role (13,14).…”
mentioning
confidence: 99%